Optimal Food Price Stabilization in a Small Open Developing Country - Gouel, Christophe; Jean, Sebastien (2012)
In poor countries, most governments implement policies aiming to stabilize the prices of staple foods, which often include storage and trade measures insulating their domestic market from the world market. It is of crucial importance to understand the precise motivations and efficiency of those interventions, because they can have consequences worldwide. This paper addresses those issues by analyzing the case of a small, open developing country confronted by shocks to both the crop yield and foreign price. In this model, government interventions may be justified by the lack of an insurance market for food prices. Considering this market imperfection, the authors design optimal public interventions through trade and storage policies. They show that an optimal trade policy largely consists of subsidizing imports and taxing exports, which benefits consumers at the expense of producers. Import subsidies alleviate the non-negativity of food storage. In other words, when stocks are exhausted, subsidizing imports prevents domestic price spikes. One striking result: an optimal storage policy on its own is detrimental to consumers, since its stabilizing benefits leak into the world market and it raises the average domestic price. By contrast, an optimal combination of storage and trade policies results in a powerful stabilizing effect for domestic food prices.